Antimicrobial, antioxidant, and cytotoxic activities of endhopitic fungi Chaetomium sp. isolated from Phyllanthus niruri Linn: in vitro and in silico studies - Rollando Rollando; Dion Notario; Eva Monica; Martanty Aditya; Rehmadanta Sitepu (The Journal of Pure and Applied Chemistry Research, 2017)
Endophytic fungi Chaetomium sp isolated from Phyllanthus niruri Linn. Mycelium powder was extracted by using ethyl acetate. Extract was fractionated using n-hexane, dichloromethane and ethanol 96%. The antimicrobial test was carried out using disc diffusion and microdilution methods. The antioxidant activity of the fraction was determined using hydrogen peroxide free radical scavenging and reducing power capacity activities. The cytotoxicity assay of the fraction against T47D breast cancer cell was carried out using dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide method (MTT). The in silico prediction of chemical substances which are reported exist in Chaetomium sp. performed using AutoDockVina embedded in PyRx version 8.0. Dichloromethane fraction was found as the most active sample against Escherichia coli (IC50 20.76 mg/mL), Staphylococcus aureus (IC50 70.15 mg/mL), Salmonella typhi (49.13 mg/mL) and was found as the most high phenolic content with value 47.44 mg GAE/g fraction, whereas the best antioxidant activity was performed by ethanol 96% fraction (85%). Cytotoxicity assay against T47D cell line showed dichloromethane fraction have highest activity with IC50 10.76 mg/mL. The docking studies showed that compounds bearing xanthone structure were potential for maltose binding periplasmic and human aromatase associating with their potencies as antibacteria and anticancer. Endophytic fungi Chaetomium sp. was isolated from Phyllanthus niruri using n-hexane, dichloromethane and ethanol fractions was studied its various biological activities as antimicrobial, antioxidant and cytotoxic agent against breast cancer cell.